Efectos jurídicos de la negativa a la realización del examen de alcohotest en contravenciones de tránsito. - Arrobo Herrera, Xiomar Gisella (2025)
In the context of criminal law, the alcohol test is an essential tool for determining the level of intoxication of drivers, which is directly related to traffic offenses. This research analyzes the legal implications of refusing to undergo the alcohol test in traffic-related cases in Ecuador. A qualitative approach was employed to gather and analyze data from various sources, including an analysis of court cases and a legal literature review. Additionally, a questionnaire based on the Likert scale was administered to judges from the Criminal Judicial Unit of Riobamba in the province of Chimborazo using probabilistic sampling techniques. The findings of this investigation revealed that the penalties for refusing the alcohol test have significant effects on both the judicial and dministrative processes. These effects impact not only the offender's presumption of innocence but also the principle of proportionality and the overall credibility of the justice system. It is concluded that treating refusal of the test as evidence of maximum intoxication infringes upon the presumption of innocence. Moreover, there is a need for differentiated sanctions that are tailored to the severity of the offending behavior.